2013
DOI: 10.1128/jcm.03422-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hourly Emergency Department Patient Volume on Blood Culture Contamination and Diagnostic Yield

Abstract: Emergency departments (EDs) are an important diagnostic site for outpatients with potentially serious infections. EDs frequently experience high patient volumes, and crowding has been shown to negatively impact the delivery of early care for serious infections, such as pneumonia. Here, we hypothesized that other important factors in the early care of infectious diseases, the rate of blood culture contamination and the accurate detection of pathogens, would be sensitive to ED operational stress, as proper colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…performed in the ED are negative in almost all cases [26], and even when positive, they only identify organisms in a few cases, and rarely alter antimicrobial management [27]. Other studies have shown that the diagnostic ability of blood cultures performed in the ED is high [28]; however, important operational factors determine their effectiveness -for example, lack of knowledge on good sampling practices [29] and ED overcrowding have been shown to degrade the performance of blood cultures, increase contamination rates, and reduce diagnostic yields [30]. A further important factor to consider is the high proportion of elderly and nursing-home residents presenting to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…performed in the ED are negative in almost all cases [26], and even when positive, they only identify organisms in a few cases, and rarely alter antimicrobial management [27]. Other studies have shown that the diagnostic ability of blood cultures performed in the ED is high [28]; however, important operational factors determine their effectiveness -for example, lack of knowledge on good sampling practices [29] and ED overcrowding have been shown to degrade the performance of blood cultures, increase contamination rates, and reduce diagnostic yields [30]. A further important factor to consider is the high proportion of elderly and nursing-home residents presenting to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued that most contamination occurred during regular daytime hours, rather than during night shifts. Other studies have found an association between increased departmental activity and BC contamination (Lee et al, 2012;Halverson et al, 2013). We did not match BC sampling times with departmental activity in this study, but this would be a useful component of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination was defined pragmatically as the presence in BC of low pathogenicity skin commensals (such as coagulase-negative staphylococci, Micrococcus species and Corynebacteria species) in patients not known to have central venous access or indwelling prosthetic material. Other similar studies have used varying definitions of BC contamination, some microbiological (Madeo et al, 2005;Gander et al, 2009;Youssef et al, 2012;Self et al, 2013) and others supplemented with clinical correlation (Schifman et al, 1998;Halverson et al, 2013;Harding and Bollinger, 2013). Our definition was primarily microbiological and was chosen for its simplicity and reproducibility without the need for access to patient records, accepting that it may modestly overestimate true BC contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Periods of increasing crowding in EDs have been associated with significant increases of BCC, suggesting that lapses in proper collection techniques by health care workers were contributory. 135 Table 3 summarizes studies that have reported successful strategies in reducing contamination rates and other associated outcomes in EDs. 53,71,78,79,[136][137][138][139][140][141][142] A common practice in Pediatric EDs is to obtain a sample for BCs simultaneously when inserting a peripheral intravenous catheter (PIV).…”
Section: Ed Interventionsmentioning
confidence: 98%